ANALYSIS OF THE APPLICATION OF BASIC TEACHING SKILLS AS PROFESSIONAL DEVELOPMENT EFFORTS FOR TEACHER IN ELEMENTARY SCHOOL - Leny Retno Indriani; Kurnia Indrawati; Khafidatun Nafi’ah; Tri Saptuti Susiani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Educators or teachers are professionals, one of the tasks of the teacher is to plan and carry out the learning process. It is stated in the Republic of Indonesia Law on the Nasional Education System. In the process of learning, there are eight basic teaching skills that needs to be mastered by a teacher. Therefore, this study aims to describe the professionalism of teacher in the application of basic teaching skills. This research is conducted by using descriptive techniques. The data of this research are qualitative data that are gained by describing the observation sheets. The result showed that all skills have been implemented by the pre-service teachers of PGSD UNS, but there are several basic skills aspect that have not been fully implemented. This aspect is create variations. Therefore, all aspects of basic teaching skills include create variations need to be implemented to develop teacher the profesionalism.